Metaphors in Nadin Amizah's Song Lyrics from the Album Untuk Dunia, Cinta dan Kotornya: A Cognitive Semantic Study - Jihan Febrianti Mokoginta; Dakia N. Djou; Nuramila (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study examines metaphors in Nadin Amizah's song lyrics from the album "Untuk Dunia, Cinta, dan Kotornya" using a cognitive semantic approach. The focus of the study includes the types of metaphors, their functions, and the meanings constructed through their use in the lyrics. The research questions focus on how metaphors are conceptually constructed, how they function in constructing poetic meaning, and how cognitive meaning patterns represent emotional and relational experiences in the lyrics. This study employed a qualitative descriptive method with an interactive model analysis of Miles and Huberman, which included data reduction, data presentation, and conclusion drawing. The types of metaphors were identified based on Lakoff and Johnson's conceptual metaphor theory, while the functions of metaphors were analyzed using Newmark's theory. Cognitive semantic meaning was examined through a mapping between the source and target domains to understand the construction of inner experience in metaphorical language. The results showed 67 metaphors, divided into structural, orientational, and ontological (container and personification) metaphors. The metaphorical functions found include referential functions, aesthetic functions, and dual functions. In addition, several cognitive meaning patterns were found, namely emotions as space or container, relationships as journeys, inner wounds as physical damage and burdens, the recovery process as a movement towards stability, and emotions as active agents. These findings confirm that metaphors in song lyrics not only function as aesthetic elements, but also as cognitive mechanisms that shape the way the lyric subject understands and represents inner experiences.